Coupling a bio-accumulator organism and MALDI-TOF MS: an early warning detection system for microcystins in water bodies - Lauceri, Rosaria (2017)
Microcystins produced by freshwater cyanobacteria pose serious threats to human health and are a growing problem in drinking water supplies worldwide. Toxin detection and identification in water reservoirs when cyanobacterial density is still low is a key step to predict harmful algal blooms and to allow the safe use of the resource. For this purpose, developing sensitive and rapid methods of analysis is crucial. Adopting a strategy that couples the use of a filter-feeder organism (Unio elongatulus, Pfeiffer 1825 (Bivalvia: Unionidae)) with matrix-assisted laser desorption ionization—time of flight mass spectrometry (MALDI-TOF MS) technology, effective microcystin detection was achieved. The performances of MALDI-TOF MS, high-liquid-performance chromatography with diode array detector (HPLC-DAD) and enzyme-linked immunosorbent assays (ELISA) test were compared. The results obtained in this study suggest that the exploitation of an efficient bio-accumulator organism, coupled with a rapid and sensitive analytical method, can be a very useful strategy in monitoring programs for early and prompt risk management.